Cognitive aspects of motor control deteriorate while off treatment following subthalamic nucleus deep brain stimulation surgery in Parkinson’s disease - Munoz, Miranda J.; Arora, Rishabh; Rivera, Yessenia M.; Drane, Quentin H.; Pal, Gian D.; Verhagen Metman, Leo; Sani, Sepehr B.; Rosenow, Joshua M.; Goelz, Lisa C.; Corcos, Daniel M.; David, Fabian J. (Frontiers in Neurology, 2024)
IntroductionThe long-term effects of surgery for subthalamic nucleus deep brain stimulation (STN-DBS) on cognitive aspects of motor control for people with Parkinson’s disease (PD) are largely unknown. We compared saccade latency and reach reaction time (RT) pre- and post-surgery while participants with PD were off-treatment.MethodsIn this preliminary study, we assessed people with PD approximately 1 month pre-surgery while OFF medication (OFF-MEDS) and about 8 months post-surgery while OFF medication and STN-DBS treatment (OFF-MEDS/OFF-DBS). We examined saccade latency and reach reaction time (RT) performance during a visually-guided reaching task requiring participants to look at and reach toward a visual target.ResultsWe found that both saccade latency and reach RT significantly increased post-surgery compared to pre-surgery. In addition, there was no significant change in Movement Disorder Society-Unified Parkinson’s Disease Rating Scale (MDS-UPDRS) Part III score.DiscussionWe found detrimental post-surgical changes to saccade latency and reach RT. We discuss the potential contributions of long-term tissue changes and withdrawal from STN-DBS on this detrimental cognitive effect.